Sistemas energéticos residenciais: avaliação do cenário atual brasileiro e alternativas para autogeração sustentável - Matheus, Ana Flávia Teixeira (2022)
From the analysis of the current landscape of the country's residential energy systems and estimates of the potential for self-production of Brazilian residences, this work proposed solutions for environmental and energy security issues in the country. This dissertation is divided into four chapters, the first being introductory, the second consisting of a literature review - which goes through the concepts of energy planning, incentive programs and legislation on the subject, distributed generation and the technologies available for the self-production of residential energy - the third, an article - in which estimates of theoretical potentials for energy use in the Brazilian residential sector are made - and finally, the fourth chapter of final considerations. Photovoltaic electricity self-production combined - or not- with solar water heating systems in Brazilian houses have a potential for reducing 7% of national electric consumption, while the use of biogas for domestic cooking without collecting domestic sewage can reduce by 4% consumption of Brazilian GLP and resolve sanitation issues for up to 32% of the population. The research is therefore in the theme of energy sustainability and represents an initial effort to draw attention to the possibility of energy re-planning from residential self-production, pointing out possible paths for the public power to foster, with incentives and investments, significant solutions for energy and environment sectors. In the end, some reflections about the contributions and limitations of the work raise questions that can be continued and deepened by future research.